Carburization behavior at elevated temperatures and mechanical properties of a hot stamped complex phase steel - Risse, Jan Henning; Sippel, Frank; Merklein, Marion (IOP Conference Series: Materials Science and Engineering, 2023)
As a lightweight construction strategy, hot stamped parts of ultra-high-strength steels with tailored properties are increasingly used for crash relevant components in car bodies, e.g., as B-pillars. With the process of tailored carburization, parts can be reinforced locally without increasing the sheet metal thickness. Thus, this process has the potential to be applied to lightweight components for no deformation zones, e.g., in the battery housings. Standardly, carburization is performed at 950 °C, with the highest strengths achieved at long times of up to 6 h, which prolongs the total process time. By raising the temperature, the carbon diffusion increases, which enables a reduced heat treatment time and, consequently, a shorter process time. Therefore, the objective of this study is to investigate the influence of elevated carburization temperatures on the mechanical properties of a carburized and hardened complex phase steel, CP-W® 800. A single carburization step at the enhanced temperatures leads to an embrittlement of the samples. Hence, an additional diffusion-annealing step is implemented to homogenize the carbon content, without enlarging the total heat treatment time. Depending on the time allocation of carburization and diffusion, the application of the diffusion annealing step results in higher strengths and ductility compared to only carburized samples.